Successful Treatment of Preterm Labor in Association with Acute COVID-19 Infection - Browne, Paul C.; Linfert, Jennifer B.; Perez-Jorge, Emilio (American Journal of Perinatology, 2020)
Novel coronavirus disease 2019 (COVID-19) infection occurring during pregnancy is associated with an increased risk of preterm delivery. This case report describes successful treatment of preterm labor during acute COVID-19 infection. Standard treatment for preterm labor may allow patients with acute COVID-19 infection to recover without the need for preterm delivery.Key Points
Keywords: COVID-19; coronavirus; pregnancy; pregnancy complication; preterm labor; azithromycin